Identification of potential managed aquifer recharge sites in hyper-arid environment using GIS and analytical hierarchy process - Hazrat Bilal (7367477) (2025)
Utilizing aquifers as groundwater storage reservoirs is an effective strategy for water management in water scare regions. The success of managed aquifer recharge (MAR) relies on the assessment and modeling of site-specific hydrogeological characteristics, including groundwater salinity, transmissivity, storativity, slope, soil properties, proximity to water recharge networks and road accessibility, etc. This study employs a GIS-based multi-criteria evaluation technique, integrating both ground and remote sensing datasets. The results indicate that a significant portion of the total land area, approximately 7,414.11 km2 (64%), can potentially be utilized for MAR practices, while the remaining 36% is restricted due to various constraints, such as built-up areas, roads, agricultural lands and nationally protected areas for conservation. The available 64% of land is further categorized into subclasses ranging from highly suitable to least suitable areas. Most of the highly and moderately suitable regions are located in the northern central parts of the country where seasonal surplus treated wastewater and desalinated water may be used to recharge groundwater. Furthermore, MAR technology can also be used to tackle saltwater intrusion in the coastal areas by injecting seasonal surplus desalinated and treated wastewater. These findings suggest that MAR technology has a high potential to facilitate aquifer water storage and recovery in the country, which can contribute to sustainable water resources. Other Information Published in: Applied Water Science License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s13201-025-02431-3